A novel biflavone from Reineckia carnea induces apoptosis of human renal cancer 786-O cells - Yang, Jianqiong; Xiao, Bang; Li, Yamei; Liu, Xiaoxuan; Zhang, Minhong; Luo, Yaoling; Wang, Biao; Liu, Hai (Frontiers in Pharmacology, 2022)
Renal cell carcinoma (RCC) is a common malignant tumor of urinary system, which is highly invasive, metastatic, and insensitive to radiotherapy and chemotherapy. Chinese herbal medicine has always been an important source of anti-tumor drug development. Reineckia carnea Kunth is a traditional herb commonly used by Miao people in southwest China. In this study, the extract of Reineckia carnea was isolated and purified by reverse phase preparative chromatography and other chromatographic techniques. According to the physicochemical properties and spectral data, the structure of the compound was identified, and a novel biflavone compound named Reineckiabiflavone A (RFA) was obtained. The result of antiproliferative activity showed that RFA had good cytotoxicity on 786-O cells with an IC50 value of 19.34μmol/L. By Hoechst 33258 apoptosis staining, typical apoptotic morphology was observed under fluorescence microscope. The apoptosis could be induced by RFA and its apoptosis rate of 786-O cells in the RFA group was increased compared with the normal control group. The cell cycle tests showed that the cells proportion was obviously arrested in the S phase. RFA could induce mitochondrial membrane potential decreased and intracellular free Ca2+ concentration increased. Western blotting showed that the expression levels of pro-apoptotic proteins (Bax, Caspase-3, Cleaved Caspase-3, and Cytochrome C) in cells increased, while the expression level of anti-apoptotic proteins (Bcl-2) decreased significantly. In conclusion, this study suggests that the compound RFA is a new biflavone, which can inhibit the proliferation and induce 786-o cell apoptosis in vitro. The apoptosis may be triggered by RFA through the mitochondrial pathway which is mediated by the overloading of intracellular calcium ion, the decreased mitochondrial membrane potential, and the expression levels of apoptosis-related proteins.